Does growth rate in spatial ability matter in predicting early arithmetic competence?. (June 2017) - Zhang, Xiao; Lin, Dan
Abstract: There is a well-established relation between overall level of spatial ability and mathematics competence: people who are stronger in the former perform better on tests of the latter. However, does the rate of growth in spatial ability also matter? This longitudinal study of Chinese children (aged three to six) demonstrated that growth rate in spatial perception during the preschool years significantly predicted arithmetic competence at the end of preschool. This effect was over and above the overall levels of spatial perception and spatial reasoning and the level and rate of growth in phonological awareness. The findings highlight the need to provide spatial learning opportunities for preschoolers whose rate of growth in this skill is slower than that of their peers. Highlights: We examine how growth rate in spatial ability predicts early arithmetic skill. Growth rate in spatial perception predicts arithmetic skill at the end of preschool. The prediction persists with the control of phonological and other spatial abilities.